Effect of process parameters on the high temperature performance and reaction mechanism of CRMA. (2nd October 2018) - Yang, Xiaolong; Shen, Aiqin; Guo, Yinchuan; Lyu, Zhenghua
Abstract: The objective of this study was to investigate the rheological properties and modification mechanism of crumb rubber modified asphalt (CRMA) with different reaction parameters. The test results indicate that the high reaction temperature can increase the rutting resistance but decreases the temperature stability of CRMA. At low reaction temperature, there is mainly swelling reaction in CRMA. However, the rubber particles begin to degrade in high temperature condition. The results can be confirmed by Fourier infrared spectroscopy (FTIR) and LMS tests. The LMS was well correlated with the rheological properties. The LMS may provide a simple means to determine the mechanical properties of binders.